Paridade de gênero na América Latina : entre uma realidade concreta e um horizonte distante - Ananda Winter Marques (2024)
Seeking to answer what explains why in some Latin American countries gender parity laws have been successfully adopted and implemented, while in others similar proposals have made little progress, this Thesis offers a comparative analysis of the different levels of success in the adoption and implementation of gender parity laws in Mexico, Panama, and Brazil. This selection presents a case where gender parity laws were successfully adopted and implemented—Mexico; a case where gender parity laws were adopted but without success—Panama; and a case where gender parity bills introduced in Parliament never reached the decision-making phase—Brazil. Utilizing the lenses and tools of feminist institutionalism, the research examines institutional contexts and their gendered aspects, considering formal and informal practices, to map obstacles and incentives to the advancement of the gender parity agenda. The comparative study of the selected cases allows for the systematization of strategies employed by agents of change and resistance and the analysis of their interactions. Thus, the Thesis contributes to a deeper understanding of the challenges and possible steps that can be taken on the path to gender parity.